Quantitative Analysis of Retinal Vasculature in Rhegmatogenous Retinal Detachment Based on Ultra-Widefield Fundus Imaging - Feng, Bingkai; Su, Wenxin; Chen, Qingshan; Gan, Run; Wang, Mingxuan; Wang, Jiantao; Zhang, Jiayi; Yan, Xiaohe (Frontiers in Medicine, 2022)
Purpose To quantitatively analyze retinal vascular morphological features, such as vascular density, caliber, and tortuosity, in rhegmatogenous retinal detachment (RRD). Methods A total of 244 patients with RRD and 400 healthy controls (HC) were included. Retinal fundus images were collected using OPTOS PLC Daytona P200T. Retinal images were divided into RRD and non-RRD regions of interest (ROIs). All visible retinal fundus vessels were then extracted mainly based on edge detection within ROI to form the whole-vascular image. Retinal vasculature parameters, such as vascular density, caliber, and tortuosity, were calculated. Results For the absolute density, the mean rank (MR) value of normal controls was significantly higher than that in non-RRD (p < 0.001). A consistent tendency of significant vascular density was increased from non-RRD to RRD (p < 0.001). The average and median diameters of normal controls were both significantly larger than RRD (p < 0.001). The average and median diameters were also appeared significantly thinner in non-RRD. Unweighted and width-inversely-weighted vascular tortuosity in RRD and non-RRD comparison exhibited non-significant differences. All types of tortuosity calculated from HC were significantly larger (p < 0.001) in values compared to RRD. All types of tortuosity values of HC were significantly higher than non-RRD. Compared with non-RRD, RRD was significantly larger in area-weighted, length-weighted, and width-weighted vascular tortuosity. Conclusions This study showed that RRD affects both the quantity and morphology of retinal vasculature, such as RRD and non-RRD areas. Smaller average and medium vascular diameters and tortuosity values were found in RRD. However, the absolute vascular density, the average and median diameter, and tortuosity values were also reduced in non-RRD although the retina is still attached. This work indicates that RRD may affect the retinal vasculature beyond the detached retina.